2017
DOI: 10.1111/ppa.12747
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of Pythium, Rhizoctonia and Sclerotinia in lettuce: association of the plant protective activity of the bacterium Paenibacillus alvei K165 with the induction of systemic resistance

Abstract: The soilborne fungi Sclerotinia sclerotiorum, Rhizoctonia solani and the oomycete Pythium ultimum are among the most destructive pathogens for lettuce production. The application of the biocontrol agent Paenibacillus alvei K165 to the transplant soil plug of lettuce resulted in reduced S. sclerotiorum, R. solani and P. ultimum foliar symptoms and incidence compared to untreated controls, despite the suppressive effect of the pathogens on the rhizosphere population of K165. In vitro, K165 inhibited the growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
1
12
1
Order By: Relevance
“…The ERF1 (Ethylene response factor 1) gene encodes a transcription factor that acts by increasing cellular ethylene production, causing senescence and, consequently, cell death, preventing disease progression to other tissues. The importance of ethylene in white mold resistance has been identified in several species such as lettuce, Brassica napus, and Arabidopsis (Fatouros et al 2017;Perchepied et al 2010;Zhao et al 2009). In the present study, no significant differences in the expression of this gene between times and genotypes were noted.…”
Section: Discussioncontrasting
confidence: 47%
“…The ERF1 (Ethylene response factor 1) gene encodes a transcription factor that acts by increasing cellular ethylene production, causing senescence and, consequently, cell death, preventing disease progression to other tissues. The importance of ethylene in white mold resistance has been identified in several species such as lettuce, Brassica napus, and Arabidopsis (Fatouros et al 2017;Perchepied et al 2010;Zhao et al 2009). In the present study, no significant differences in the expression of this gene between times and genotypes were noted.…”
Section: Discussioncontrasting
confidence: 47%
“…T. harzianum strain T22 is one of the best characterized and commercialized Trichoderma strains. It effectively antagonizes soil pathogens (Wilson et al, 2008;Percival et al, 2011;Roberti et al, 2015;Fatouros et al, 2018) and can trigger ISR against diverse above-and belowground attackers (Tucci et al, 2011;Vitti et al, 2016;Coppola et al, 2017Coppola et al, , 2019Debode et al, 2018;Pocurull et al, 2020;Alınç et al, 2021). Besides promoting plant growth, T. harzianum ESALQ1306 has been shown to highly reduce Sclerotinia sclerotiorum disease severity through parasitism and to induce ISR against spider mites (Geraldine et al, 2013;De Oliveira et al, 2018;Barroso et al, 2019;Canassa et al, 2020).…”
Section: Selecting a Potentially Powerful Pool As Step Onementioning
confidence: 99%
“…FP12 and Arthrobacter sp. FP15 [ 15 , 17 , 18 , 19 ], we investigated their capacity to protect grape berries against A. carbonarius and B. cinerea , along with their plant defense triggering activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that strain K165 can protect plants from various soil-inhabiting pathogens such as Verticillium dahliae , Fusarium oxysporum f.sp. melonis , and Pythium ultimum , reducing disease severity by 50% compared with controls [ 13 , 14 , 15 ]. The plant protective activity of K165 lies mostly in its plant recognition by the FLS2 receptor and the subsequent induction of systemic resistance [ 16 ].…”
Section: Introductionmentioning
confidence: 99%